East Asia Update, March 2006 : Solid Growth, New Challenges - World Bank (World Bank, Washington, DC, 2020)
The report stipulates growth in Emerging East Asian countries eased modestly from 7.5 percent in 2004 to 6.8 percent in 2005. The slower pace of activity was most clear in the Newly Industrialized Economies (NIEs), and in some of the middle income economies of South East Asia. But it was not universal. Growth accelerated in Indonesia and Vietnam, and continued at very high rates in China. In addition, while the moderation in activity in the NIEs and South East Asia occurred in the first part of 2005, activity was generally rebounding in the latter part of the year. Indeed growth for 2005 as a whole, generally turned out higher than we had expected six months ago. The prospects for 2006 also look reasonably firm, with aggregate regional growth expected to exceed 6.5 percent for a third year in a row. Global high tech demand slowed in late 2004 and early 2005, causing a downturn in tech-reliant East Asian export growth, but then rebounded strongly in the second half of the year. High oil prices clearly played a large role in moderating growth in 2005. While the report assumes that oil prices have now peaked, they are still expected to average 10 percent higher in 2006 than in 2005, so that some of the adverse impact is still likely to be playing out in 2006. Nevertheless, the real surprise has been that the highest real oil prices in more than 25 years did not inflict more serious economic damage, with growth not falling below 4 percent in any of the main economies of the region.